2019
DOI: 10.7454/jki.v22i2.873
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Kemampuan Kepala Keluarga Dalam Memenuhi Kebutuhan Ekonomi Keluarga: Studi Fenomenologi Pengalaman Orang Dengan Gangguan Jiwa Paska Pasung

Abstract: Decreasing the Capabilities of the Breadwinner in Meeting the Economic Needs of Families: A phenomenology Study of the Mental Illness People Post-Pasung. The breadwinner of the family economically responsible for meeting the needs of all family members, including clothing, food, and housing needs. A breadwinner of the family with mental illness after pasung needs to adjust to social functions including the ability to work and be involved in social relations. Pasung is physical restraint and confinement by fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…However, the neighbors and the environment were fully supportive for the breadwinner to continue working by giving support for casual work like domestic chores. This support increased their confidence and was a strong basis for them to continue their role as head of the family 7 Daulima (2018) [ 31 ] The validity and reliability results showed that the content of this instrument is valid once improvements had been made to the statement item numbers 16 and 17. It was also shown to be reliable by the consistency of the responses with an alpha value of .729.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the neighbors and the environment were fully supportive for the breadwinner to continue working by giving support for casual work like domestic chores. This support increased their confidence and was a strong basis for them to continue their role as head of the family 7 Daulima (2018) [ 31 ] The validity and reliability results showed that the content of this instrument is valid once improvements had been made to the statement item numbers 16 and 17. It was also shown to be reliable by the consistency of the responses with an alpha value of .729.…”
Section: Resultsmentioning
confidence: 99%
“…Helena, Daulima and Wardani [ 37 ] also identified that the family experienced a psychosocial change after their family member was placed in pasung, mainly if the person had previously been the head of the household or primary breadwinner. In these circumstances, other family members now had to find new ways of gaining income for the family or taking on the role as head of household [ 29 , 31 ]. Consequently, many families with a PWMD lived in poverty.…”
Section: Resultsmentioning
confidence: 99%
“…Pasung is usually done in anything from over a few days to years (Hartini, Fardana, Ariana, & Wardana, 2018). About 90% of cases of pasung are performed in schizophrenia patients who are accompanied by aggressive behavior and hallucinations that risk in injuring themselves, others, and damaging the surrounding environment (Daulima, Rasmawati, & Wardani, 2019;Menteri Kesehatan Republik Indonesia, 2017).…”
Section: Schizophreniamentioning
confidence: 99%
“…Indonesia has included as a high mortality and disability rate countries because of high schizophrenia cases than other countries in the world (2). According to the data of Indonesia Basic Health Research (Riskesdas), the occurrence of mental health problems in 2013 consisted of 1.7% per mill (3) with stocks occurrence percentage from 14.3% (4) and raised into 7.0% per mill in 2018 (5,6). Riskesdas also notes that the stocks occurrence rate in 2018 was still 14%.…”
Section: Introductionmentioning
confidence: 99%
“…They are designed to restrict the patient's movements and made from wooden bars. The patients are chained or locked in a special room (4,5). Various reasons were uttered by the family when such action was undertaken on individuals with mental health disorders.…”
Section: Introductionmentioning
confidence: 99%